A GEOGRAPHICAL INTEGRAL APPROACH OF PROTECTED AREAS. THE CASE OF LA PAMPA - Valeria Soledad Duval (Boletín Geográfico)
Protected areas are spaces to be preserved, so they should be studied as a system from an integral vision. Components of natural and socio-cultural environment are geographically analyzed in an interrelated way to understand the system and to provide solutions to issues that occur in these places. The study includes transversal concepts to the analysis variables: multiscalarity and multitemporality. The aim of the paper is to propose the study of protected areas from an integral vision under a geographical perspective. This is why the explanation of the theoretical approach propose the selection and analysis of variables for the study of protected areas. Scientific articles made on protected areas in La Pampa Province were analyzed and proved that this approach is currently not considered. A case study was presented in which strengths and weaknesses of a holistic approach were analyzed.